2013
DOI: 10.7314/apjcp.2013.14.5.3255
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes and Prognostic Factors Associated with the Response to Erlotinib in Non-Small-Cell Lung Cancer Patients with Unknown EGFR Mutational Status

Abstract: Background: The efficacy of erlotinib is controversial in patients with unknown EGFR mutational status. The aim of this study was to identify the clinicopathological factors that are predictive of erlotinob treatment outcomes for NSCLC patients with unknown EGFR mutational status. Materials and Methods: A retrospective analysis of 109 patients with advanced NSCLC who had previously failed at least one line of chemotherapy and received subsequent treatment with erlotinib (150 mg/day orally) was performed. A Cox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…Therefore, we were able to achieve a 58.9% disease control rate (ORR + SD). Side effects were predictable and manageable, similar to those seen in previous erlotinib clinical trials [8,[11][12][13][14][15]. The median PFS and OS of the study population were 242 and 377 days, respectively, which were similar to those reported in other similar studies [8,[11][12][13][14][15].…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, we were able to achieve a 58.9% disease control rate (ORR + SD). Side effects were predictable and manageable, similar to those seen in previous erlotinib clinical trials [8,[11][12][13][14][15]. The median PFS and OS of the study population were 242 and 377 days, respectively, which were similar to those reported in other similar studies [8,[11][12][13][14][15].…”
Section: Discussionsupporting
confidence: 85%
“…The efficiency of EGFR-TKIs is unclear in patients without mutational analysis (Aydiner et al, 2013). Combined with the previous reports (Okamoto et al, 2005), which proved that the serum CEA level was an independent predictive factor of clinical efficacy of EGFRTKIs, patients with elevated serum CEA level before the initial treatment may be screened for EGFR-TKI treatment under the condition that we couldn't obtain specimens for gene detection.…”
Section: Discussionmentioning
confidence: 99%
“…There are hardly any favorable therapies for patients with middle and advanced NSCLC due to its increasing morbidity and mortality (Wu, 2012;Han et al, 2013;Liang et al, 2013). Genetic markers, tumor vessels and T cell receptors are frequently used as the targets of molecular targeted therapy for lung cancer, in which epidermal growth factor receptor (EGFR) is the major one at present (Aydiner et al, 2013;Tomonaga et al, 2013;Wheler et al, 2013). With the development of human immunology and molecular biology, people have gained profound recognition of tumor markers and targeted molecules with marvelous achievements.…”
Section: Discussionmentioning
confidence: 99%